1973
DOI: 10.1029/ja078i025p05751
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the magnetospheric barium release

Abstract: The magnetospheric barium release experiment of September 21, 1971, was observed by a high‐performance image intensifier television camera system from Kitt Peak National Observatory, Tucson, Arizona. The system produced high‐resolution video recordings of the dynamic morphology of the barium ion cloud. The system was calibrated for absolute sensitivity, thus enabling the reconstruction of the barium density profiles in the cloud. The ionized plasma expands along the field line with the velocity somewhat greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
(11 reference statements)
1
14
0
Order By: Relevance
“…(1) at I min after a release at 31,000 km Mende [1973] observed Ba + expanding slightly beyond the neutral cloud, suggesting a slight but detectable acceleration, and (2) Haerendel et al [1971] reported that sensitive TV images showed ions at 1150 km after 750 s following a 930 km middle latitude sounding rocket release even though film records did not show the high velocity tail in the initial distribution which would be required for this observation. It was speculated that a high velocity tail in the ion distribution might result from the pulling action of the photoelectrons that were produced with excess energy.…”
Section: Previous Observations Of the Initial Expansion Of Ba + Alongmentioning
confidence: 88%
“…(1) at I min after a release at 31,000 km Mende [1973] observed Ba + expanding slightly beyond the neutral cloud, suggesting a slight but detectable acceleration, and (2) Haerendel et al [1971] reported that sensitive TV images showed ions at 1150 km after 750 s following a 930 km middle latitude sounding rocket release even though film records did not show the high velocity tail in the initial distribution which would be required for this observation. It was speculated that a high velocity tail in the ion distribution might result from the pulling action of the photoelectrons that were produced with excess energy.…”
Section: Previous Observations Of the Initial Expansion Of Ba + Alongmentioning
confidence: 88%
“…Called striation development, the process has been ascribed by most authors to the gradient E x B instability [Linson and Workman, 1970;Vi51k and Haerendel, 1971], which is related to the differential motion of the barium ions with respect to the neutral wind. Striations also have been observed to develop in barium thermite releases at very high altitudes in the magnetosphere, where there is no neutral atmosphere [l•61k and Mende, 1973]. In these cases, the early striations are thought to arise from a Rayleigh-Taylor instability during the deceleration phase of the expansion of the ion cloud [Haerendel and L'•t, 1970;Pilipp, 1971 ].…”
Section: Discussionmentioning
confidence: 99%
“…One interestng problem that requires further investigation is the dynamics of a high speed plasma cloud moving transverse to the ambient geomagnetic field. Experimentally this phenomenon has been studied using shaped charge barium releases (Wescott et al, 1980;Simons et al, 1980;Koons and Pongratz, 1981) and rocket barium releases (Mende, 1973;Brence et al, 1973;Heppner et al, 1981), and will be a major part of the scientific studies for the upcoming CRRES mission (Combined Release and Radiation Effects Satellite) sponsored by NASA and the Air Force. It should be noted that the high speed releases to date have been relatively small (barium vapor less than 1 kg) compared to those planned for the CRRES mission (up to 10 kg of barium vapor).…”
Section: (Continue On Reverse If Necessary and Identify By Block Number)mentioning
confidence: 99%